Site-specific characterization of SARS-CoV-2 spike glycoprotein receptor-binding domain. (3rd September 2020) - Antonopoulos, Aristotelis; Broome, Steven; Sharov, Victor; Ziegenfuss, Christopher; Easton, Richard L; Panico, Maria; Dell, Anne; Morris, Howard R; Haslam, Stuart M
Abstract: The novel coronavirus SARS-CoV-2, the infective agent causing COVID-19, is having a global impact both in terms of human disease as well as socially and economically. Its heavily glycosylated spike glycoprotein is fundamental for the infection process, via its receptor-binding domains interaction with the glycoprotein angiotensin-converting enzyme 2 on human cell surfaces. We therefore utilized an integrated glycomic and glycoproteomic analytical strategy to characterize both N- and O- glycan site-specific glycosylation within the receptor-binding domain. We demonstrate the presence of complex-type N-glycans with unusual fucosylated LacdiNAc at both sites N331 and N343 and a single site of O-glycosylation on T323.